If it's not what You are looking for type in the equation solver your own equation and let us solve it.
26=5(u+8)-7u
We move all terms to the left:
26-(5(u+8)-7u)=0
We calculate terms in parentheses: -(5(u+8)-7u), so:We get rid of parentheses
5(u+8)-7u
We add all the numbers together, and all the variables
-7u+5(u+8)
We multiply parentheses
-7u+5u+40
We add all the numbers together, and all the variables
-2u+40
Back to the equation:
-(-2u+40)
2u-40+26=0
We add all the numbers together, and all the variables
2u-14=0
We move all terms containing u to the left, all other terms to the right
2u=14
u=14/2
u=7
| 7x-6=7x+2-8 | | 11=11w+44 | | 3x+5=4x+3x-4 | | 6c³;c=2 | | Y=7(2y) | | 5x+10-2x-4=3(x+2) | | 4=h/2+3 | | 378=9x= | | 6c3;c=2 | | 12=3x+10x-14 | | -29=6+8(f+3) | | 10−5y−4=–10−9y | | 2y-3y=3 | | 1/2x16=36 | | 4n+12=4n+12= | | 4q-5=6q+5 | | 4x+19=19+x+15 | | -1/3x-5/2=5/2 | | -3-x/3=1.5 | | -30=n-7 | | 8x-4=5x-4 | | -6.9n=69 | | 13=4+b2 | | 17=3x+11x-11 | | (4+8/2x(6-3)=) | | -6+6g=5g | | 144=9x+46 | | 4-55x=11 | | −10=2x−6 | | -4(m+7)=24 | | -5a+54=24 | | -6+6g=-g |